Development of high efficiency combustor system for industrial furnace - Puteri Norfazreen, Razali (2012)
Nowadays, there are many researches that include high temperature of combustion. This research developed high efficiency combustor system for industrial furnace. Objectives of this research are to study the performance of combustion system and propose a new design of combustor system for industrial furnace. 99.5% of pure zinc was heated in the furnace within two hours and the sprue gas went through nanoparticle collector. The apparatus involved in this experiment are diesel blower, cooling tower, circulating pump, collector tank, furnace, infrared thermometer and thermocouples. All the temperatures distribution from the furnace until the nanoparticle collector system is measured. The result obtained is collected and there are three samples were provided. The smallest particle size obtained from the ZnO is !03"! ƞm and the largest size is 12"# µm. At 300 second highest temperature in the furnace was at channel 6 which is 1069.52 oC while the lowest temperature obtained at channel 16 which is 139.06 °C. The proposed design is able to produce zinc oxide but not able to achieve nano size particle. The recommendations that can be used for future works are change the nano cloth to smaller nano filter and these samples should be test to validate their properties.